Identification of a period of renal ischemic vulnerability studying the changes in the indicators of acute renal insufficiency after heart surgery with extracorporeal circulation. - Barata, J D (1992)
We studied the pre operative status and the 1st, 4th, 12th and 24th hours of the post operative period after open heart surgery with cardiopulmonary bypass with a crystalloid solution containing 10 gr of mannitol. We considered acute renal failure (ARF) as being any increase in plasma creatinine values of 0.25 mg/dl for the first 24 hours and 0.5 mg/dl for periods longer than 24 hours. Six patients had transitory ARF (28.5%). The maximum value of plasma creatinine was 2.3 mg/dl and no patients required renal function substitution. There were no deaths. We used as ischemia ARF indicators the urinary flow rate, urine/plasma creatinine ratio, urine/plasma osmolality ratio, sodium fractional excretion and free water reabsorption. We also measured the urinary N-A-Glucosaminidase (NAG). We found that creatinine clearance reached its lowest in the first and fourth hours. Beyond the fourth hour we observed, the urinary flow rate reduce significantly, the urine/plasma creatinine and osmolality ratios reach values traditionally associated prerenal ARF, an increase main free water reabsorption and a decrease in sodium fractional excretion with a close relationship between the less than 1 value and the increase in plasma creatinine. There was a significant NAG increase in the 24 th hour. The evidence of a vulnerability period for renal ischemic lesions between the 4 th and 12 th hour suggests a second mannitol administration during the first four hours of the post operative period.